Brood size of three swimming crabs from the Gulf of California, Mexico (Decapoda: Portunidae) - Solís-Ibarra, R. (1996)
Since 1950 a large commercial shrimp trawler neet has operated in the Gulf of California and off the Pacific coast of Mexico (Paul & Hendrickx 1980). Portunid crabs are an important pan of the shrimp by-catch, with densities as high as 16,9 kg/ha (Hendrickx 1985). Sore aspects of The biology of portunid crabs from the coastal zone in Ihe Gulf of California have been investigated (Paul & Hendrickx 1980, Paul 1981, 1982).